Subsidiary Financing: Risk Shifting as a Commitment Device - Lóránth, Gyöngyi; Morrison, Alan D; Zeng, Jing (The Review of Corporate Finance Studies, 2026)
Abstract We study how firms can design their organizational structures to overcome dynamic commitment problems when entering new markets. A manager exerts costly effort to first develop and subsequently manage an investment opportunity. Ex post, the firm underinvests in projects that generate high management rents. However, the prospect of those rents helps offset the manager’s initial project development cost, making ex ante commitment to invest optimal. Levered subsidiaries mitigate this time-consistency problem by introducing risk-shifting incentives that counteract underinvestment. Subsidiaries are most valuable for projects that are costly to develop, have moderate management costs, and yield returns uncorrelated with existing business. (JEL G32, G34, L22)